Community-Based Tourism in Protected Areas: Elaborating A Model from A South African Perspective - Andrea GİAMPİCCOLİ (Akdeniz University Tourism Faculty, 2021)
Community-based ecotourism (CBET) shares many of the values and challenges of community-based tourism (CBT) but must also consider the interaction of local communities and the environment, often in areas of controlled or restricted use. Although CBT and CBET have been part of South Africa’s economic strategy, governance, and social structures and hierarchies may constrain opportunities for entry. This article reviews the relevant literature with specific reference to South African CBT and CBET enterprises and uses the iSimangaliso Wetland Park as a case study to build a general framework for CBT around conservation areas. In particular, the framework describes a pathway for CBET ventures to move from an internal partnership model to an external model and ultimately complete self-sufficiency and independence if desired. We show that despite numerous challenges, CBET can be viable in conservation areas, provided all parties involved in the venture make a concerted effort to ensure that the main objectives of poverty alleviation and improved environmental management are met.